The effects of fumonisins on sphinganine and sphingosine levels in hepataocyte cultures, experimental animals and humans - Van der Westhuizen, Liana (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2000.